Behavioural responses of infective‐stage copepodids of the salmon louse (Lepeophtheirus salmonis, Copepoda:Caligidae) to host‐related sensory cues. Issue 6 (17th September 2017) - Fields, D M; Skiftesvik, A B; Browman, H I
Abstract: The salmon louse ( Lepeophtheirus salmonis [Krøyer]) is an ectoparasitic copepod that causes disease in farmed Atlantic salmon ( Salmo salar ) and may play a role in the decline of some wild salmonid populations. Controlling lice infestations is a major cost for the salmon industry; this has stimulated the pursuit of alternative approaches to controlling them. One such approach involves determining, and then disrupting, the sensory cues used by the parasite to find its host. In this context, we examined the behavioural responses of lice copepodids to light flicker—simulating light reflecting from the sides of the salmon host and/or the shadows cast by fish passing overhead—and water‐soluble chemicals released from the skin of the salmon. From these observations, we estimate that visual cues such as those presented here would operate at relatively long range (metres to tens of metres). A diffuse host‐related olfactory cue stimulated swimming, however, it remains unclear whether olfactory cues provide directional information. The observations presented herein could be used to disrupt the link between the parasite and host fish, using a large number of traps deployed at a distance from a salmon farm, for example, thereby reducing sea lice infestation pressure.